Cavovarus With a Twist: Midfoot Coronal and Axial Plane Rotational Deformity in Charcot-Marie-Tooth Disease. (May 2022) - An, Tonya; Haupt, Edward; Michalski, Max; Salo, Jari; Pfeffer, Glenn
Background: The cavovarus deformity of Charcot-Marie-Tooth (CMT) disease is often characterized by a paradoxical relationship of hindfoot varus and forefoot valgus. The configuration of the midfoot, which links these deformities, is poorly understood. Accurate assessment of 3-dimensional alignment under physiologic loadbearing conditions is possible using weightbearing computed tomography (WBCT). This is the first study to examine the rotational deformity in the midfoot of CMT patients and, thus, provide key insights to successful correction of CMT cavovarus foot. Methods: A total of 27 WBCT scans from 21 CMT patients were compared to control WBCTs from 20 healthy unmatched adults. CMT patients with a history of bony surgery, severe degenerative joint disease, or open physes in the foot were excluded. Scans were analyzed using 3-dimensional software. Anatomic alignment of the tarsal bones was calculated relative to the anterior-posterior axis of the tibial plafond in the axial plane, and weightbearing surface in the coronal plane. Results: Maximal rotational deformity in CMT patients occurred at the transverse tarsal joints, averaging 61 degrees of external rotation (supination), compared to 34 degrees among controls ( P < .01). The talonavicular joint was also the site of peak adduction deformity in the midfoot, with an average talonavicular coverage angle measuring 12 degrees compared with −11 degrees in controls ( P < .01). Conclusion: This 3-dimensional WBCT analysis is the first to isolate and quantify the multiplanar rotational deformity in the midfoot of CMT patients. Compared with healthy unmatched control cases, CMT patients demonstrated increased axial plane adduction and coronal plane rotation at the talonavicular (TN) joint. These findings support performing soft tissue release at the TN joint to abduct and derotate the midfoot as a first step for targeted deformity correction. Level of Evidence: Level III, retrospective case-control study.